Proceedings of the 4th International Conference on the Durability of Concrete Structures 2014
DOI: 10.5703/1288284315481
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Micro and Macro Cracks Due to Sustained Loading on Chloride-Induced Corrosion of Reinforced Concrete Beams

Abstract: Chloride-induced corrosion of steel is one of the most commonly found problems affecting the durability of reinforced concrete structures in both marine environment and where de-icing salt is used in winter. As the significance of micro-cracks on chloride induced corrosion is not well documented, 24 reinforced concrete beams (4 different mixes -one containing Portland cement and another containing 35% ground granulated blastfurnace slag at 0.45 and 0.65 water-binder ratios) were subjected to three levels of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It has been suggested that the fatigue load process leads to cracks in concrete structures, and the generation of cracks accelerates the corrosion of rebar steel in concrete. Wang et al [31] concluded that the load level directly affected the rate of the corrosion of reinforcement within concrete, and that microcracks generated by the fatigue load had a greater effect on the corrosion of reinforcement in concrete than macro-cracks, but to some extent, micro-cracks could heal and reduce the corrosion. Fu et al [32] also found that the presence of transverse fissures in the tensile surface of RC aggravated the corrosion of the reinforcements.…”
Section: Durability Performance Of Reinforced Concrete Under Fatigue ...mentioning
confidence: 99%
“…It has been suggested that the fatigue load process leads to cracks in concrete structures, and the generation of cracks accelerates the corrosion of rebar steel in concrete. Wang et al [31] concluded that the load level directly affected the rate of the corrosion of reinforcement within concrete, and that microcracks generated by the fatigue load had a greater effect on the corrosion of reinforcement in concrete than macro-cracks, but to some extent, micro-cracks could heal and reduce the corrosion. Fu et al [32] also found that the presence of transverse fissures in the tensile surface of RC aggravated the corrosion of the reinforcements.…”
Section: Durability Performance Of Reinforced Concrete Under Fatigue ...mentioning
confidence: 99%
“…On the other hand, controversial results have been reported on corrosion rate and corrosion propagation time 10,11 . Reduced corrosion initiation times in cracked RC have been reported in several studies, 12–15 associated to an increase in corrosion rate during propagation stage, 12,13 which could anyway be more marked for short exposure times, decreasing with time 10,14 and become negligible in the long‐term 15 . At this regard, more studies considering natural propagation of corrosion in presence of cracks would be useful to deepen the knowledge on the corrosion propagation phase, since many studies involve accelerated corrosion (through the application of an external current), which anyway may be not fully representative of corrosion in real structures 16 …”
Section: Introductionmentioning
confidence: 98%
“…Micro cracks are the outcome of poor workmanship, low quality material, and inadequate mixing, as well as the environment during the concrete pouring. Though these cracks have a minor impact on natural frequencies and mode shapes, but they can prompt corrosion of reinforced steel [6]. Macro cracks, on the other hand, alter the natural frequencies and mode shapes of the members.…”
Section: Introductionmentioning
confidence: 99%